Critical hydrogen concentration of hydrogen-natural gas blends in clathrate hydrates for blue hydrogen storage. (May 2021) - Moon, Seokyoon; Lee, Yunseok; Seo, Dongju; Lee, Seungin; Hong, Sujin; Ahn, Yun-Ho; Park, Youngjune
Abstract: The so-called blue hydrogen production process, integrates conventional fossil fuel-based production methods with carbon capture and storage technologies. This combination reduces total CO2 emissions, compared to conventional grey fossil-fuel-based hydrogen production, and can be implemented more rapidly than renewable energy-based water-splitting green hydrogen production. Recently, hydrogen-natural gas blends (HNGB) have been proposed as a practical near-term option, because the blended H2 can be transported through existing natural gas pipelines. Clathrate hydrates could be a feasible way to store the HNGB in intermediate fuelling stations. In this study, we investigated and determined the critical hydrogen concentration (CHC) of HNGB hydrates and their formation kinetic patterns. The results suggest that including natural gas components (e.g., CH4 and C2 H6 ) significantly affects the level of H2 occupation in the structural cages of the clathrate hydrates. Multiple hydrogen molecules were observed to occupy both small and large cages in all cases. Specifically, up to two and four H2 molecules occupied small and large cages, respectively, of the synthesized clathrate hydrate, which exhibited a critical H2 concentration when the feed gas ratio of CH4, C2 H6, and H2 was 27:3:70 mol%. The kinetic properties were also determined for designing clathrate-based HNGB storage media. These findings provide practical insights for developing clathrate hydrate-based HNGB storage media and transportation systems in the near future. Highlights: HNGB hydrates were investigated for blue hydrogen storage and transportation. Critical hydrogen concentration and the formation kinetic patterns of HNGB hydrates were explored. Natural gas components significantly affect H2 occupation in the hydrates' cages. The maximum H2 occupancy of sII hydrates was experimentally observed. The findings provide insights for designing hydrate based HNGB storage media.